High levels of susceptibility to new and older antibiotics in Neisseria gonorrhoeae isolates from Saskatchewan (2003–15): time to consider point-of-care or molecular testing for precision treatment?. (27th September 2017) - Thakur, Sidharath D; Levett, Paul N; Horsman, Gregory B; Dillon, Jo-Anne R
Abstract: Objectives: The antimicrobial susceptibility of Neisseria gonorrhoeae isolates from Saskatchewan was determined retrospectively (2003–15) to ascertain temporal trends to both current and older antimicrobials used for treatment. Method: The agar dilution method was used to test the antimicrobial susceptibilities of 685 isolates to seven antibiotics. Results: Over the period, only three (0.4%) gonococcal isolates had reduced susceptibility to cefixime and/or ceftriaxone. All isolates were susceptible to spectinomycin. Over 95% of the isolates tested were susceptible to azithromycin except in 2010 and 2013 (27.6% and 7.2% resistant, respectively). One isolate was resistant to both azithromycin and cefixime. Ciprofloxacin resistance was seen in < 5% of isolates prior to 2010, but in > 5% thereafter. From 2006 to 2012, and in 2015, penicillin resistance was detected in < 5% (0%–4.0%) of isolates, but in > 5% for the rest of the study period. Tetracycline resistance remained >5% (11.8%–89.1%) throughout the study. Plasmid-mediated resistance to tetracycline fluctuated between 0% and 17.5% of isolates tested. Four isolates were MDR and two isolates were XDR. Conclusions: N. gonorrhoeae isolates were largely susceptible (∼85%) to antibiotics no longer recommended for treatment, such as penicillin and ciprofloxacin. Gonorrhoea in Saskatchewan is primarily (>95%) diagnosed by nucleic acid amplification testing, which does not permit antimicrobial susceptibility testing. The development of molecular testing, or point-of-care tests, to evaluate antimicrobial susceptibility, would enhance knowledge of true levels of resistance and allow discretion as to whether older but still effective antibiotics could be used in individual patient care.